Caracterização das condições acústicas de salas de aula destinadas ao ensino da música na educação básica - Viero, Claudia Rogeria Gaida (2012)
The acoustic inadequacy in an environment for teaching and study of music can trigger problems in the process of learning music, because the music content or the speech itself, can be modified, creating possibilities of erroneous adaptations to inadequate conditions. Because of this, there is concern with the implementation of Law nº. 11 769/2008 that amends Law no. 9.394/1996 - Law of Guidelines and Bases of Education (LDB), which inserts the teaching of music in primary education on a mandatory way, but not exclusive in the school curriculum. This study aims to contribute to the integration of music in schools so that it can be done correctly, providing to the public school the opportunity to experience this learning. Therefore, it aims to propose recommendations for the adaptation of the existing rooms events, lectures and musical activities in the schools of the state. It was used as a sample, five different types of rooms existing in the state of basic education in Santa Maria - RS which are characterized by architectural forms and construction set in the '70s, '80s and '90s. We collected information on dimensions, geometry and materials, having as goal, to evaluate the acoustics of the rooms. We evaluated the acoustic characteristics of the room, with and without furniture, using measures to determine the impulse response of the acoustic parameters (ISO 3382/2009), of verify the acoustic quality (clarity of musical sounds) and the speech intelligibility. These acoustic parameters are the Reverberation Time, Decay Time Initial, Clarity, Definition and Speech Transmission Index. The evaluation results showed the reverberation times and acoustic parameters of the rooms to be unsuitable for music. There was a determination, through trials in reverberation room (ISO 354/2003),of the sound absorption of classes, chairs, backpacks and other common objects in classrooms. This a showed that the furniture has great influence on the behavior of absorption of the room, changing the experimental results when performed with the furnished room. But does not mean to be a solution to the acoustics conditions of the rooms studied, but rather a guide to possible modifications of the rooms, materials and furnishings. Thus, recommendations were proposed to the adaptation of the rooms now used for events, lectures and musical activities in the schools of the state, fulfilling the proposed objective.